Natural Sciences, Management Theory, and System Transformation for Sustainability. Issue 1 (January 2021) - Wasieleski, David; Waddock, Sandra; Fort, Tim; Guimarães-Costa, Nuno
It is becoming clear that many of today's management theories are inadequate theoretically and practically to move understanding, scholarship, and practice to where it needs to be for scholars, business leaders, and policy makers to cope with an increasing fraught world. This Special Issue's focus is on sustainability. Sustainability challenges need to incorporate multidisciplinary interventions and the trans- and interdisciplinary nature of solutions. To actively seek transformation toward sustainability, fundamental and innovative short-term as well as long-term efforts are required in society, economy, technology, and education, including our understanding of human behavior and attitudes toward the management of the environment. This introductory piece presents natural science theories as a promising approach for achieving progress toward transformation for sustainability.